Backyard Sugarcane - Leslie Baucum; Ronald W. Rice; Lester Muralles (EDIS)
Revised! SS-AGR-253, a 5-page fact sheet by L. Baucum, R.W. Rice, and L. Muralles, informs homeowners of the types and varieties of sugarcane, site selection, planting material, planting, early care, formation of the stool, pest management, harvesting, and overwintering. Published by the UF Department of Agronomy, October 2009.